Al-Qur’ān al-Karīm: Mauqifuh wa Waẓīfatuh min Khilāl Takāmul al-Ma‘ārif wa al-Qiyam al-Indūnīsiyyah fī al-Dirāsāt al-Islāmiyyah - Hamka Hasan; Didin Saepuddin; JM Muslimin (JOURNAL OF QUR'AN AND HADITH STUDIES, 2021)
This article discusses the position of the holly Quran in the integration of Knowledge and Indonesian-ness in Islamic studies by analyzing on the Dissertation of the Graduate School of UIN Syarif Hidayatullah Jakarta students. The method used in this research is qualitative literature which makes 152 dissertations written in the period 2010-2015 as the object of study. The study discovered that the integration in the dissertation is seen at the theoretical and substantive levels. Theoretically, all dissertations make the verses of the Quran and the Prophet's Hadith a theoretical framework integrating with the theory of the field of science according to the theme studied. Likewise, in terms of substance, all the themes of the dissertation are related to Islam both as a perspective and as an object of study present the Quran and Hadith as the basis of their argument. Regarding Indonesian-ness, carried scientific integration is in accordance with the local context and dynamics. This locality is very dominant because whatever the methodology used in conducting the dissertation, the dominant theme written is about Indonesian-ness.